Epilepsy Mechanisms in Neurocutaneous Disorders: Tuberous Sclerosis Complex, Neurofibromatosis Type 1, and Sturge–Weber Syndrome - Stafstrom, Carl E.; Staedtke, Verena; Comi, Anne M. (Frontiers in Neurology, 2017)
Neurocutaneous disorders are multisystem diseases affecting skin, brain, and other organs. Epilepsy is very common in the neurocutaneous disorders, affecting up to 90% of patients with tuberous sclerosis complex and Sturge-Weber syndrome, for example. The mechanisms underlying the increased predisposition to brain hyperexcitability differ between disorders, yet some molecular pathways overlap. For instance, the mechanistic target of rapamycin (mTOR) signaling cascade plays a central role in seizures and epileptogenesis in numerous acquired and genetic disorders, including several neurocutaneous disorders. Potential routes for target-specific treatments are emerging as the genetic and molecular pathways involved in neurocutaneous disorders become increasingly understood. This review explores the clinical features and mechanisms of epilepsy in three common neurocutaneous disorders – tuberous sclerosis complex, neurofibromatosis type 1, and Sturge-Weber syndrome.